role of religious minorities’ deputies in the Iranian National Consultative Assembly towards the most prominent economic and social issues 1906-1915 - Jabr, Ass.Prof Dr.Hayder Abdel-Aali (Thi Qar Arts Journal, 2023)
The study of the roles of minority deputies in the Iranian National Consultative Assembly is an important study, especially since the previous scientific studies related to this topic were not mentioned by Iraqi academic researchers except in a limited way. Therefore, we resorted to choosing this topic to rely on the lectures of the Iranian National Consultative Assembly and its laws during the period (1906-1915), and the reason for choosing the study period since 1906, which is the year that witnessed the writing of the first constitution for Iran after the constitutional revolution; It was followed by the enactment of the Iranian National Consultative Assembly elections law and as a result of which the first legislative session of the council was held in 1906. The determination of 1915 came as a result of the suspension of the council’s work in its third legislative session following the events of World War I and the entry of Allied forces into Iranian territory; Which led to the disruption of the council.